2010
DOI: 10.1128/aac.01762-09
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Biochemical Comparison of the Carbapenem-Hydrolyzing Activities of Five Plasmid-Borne AmpC β-Lactamases

Abstract: The CMY-2, ACT-1, DHA-1, ACC-1, and FOX-1 enzymes are representative of five plasmid-mediated AmpC (pAmpC) ␤-lactamase clusters. Resistance to imipenem has been reported in Enterobacteriaceae as a result of pAmpC expression combined with decreased outer membrane permeability. The aim of this study was to determine the role of different pAmpCs in carbapenem resistance and to define the structure/activity relationship supporting carbapenemase activity. The ampC genes encoding the five pAmpCs and the chromosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 32 publications
4
83
0
5
Order By: Relevance
“…The carbapenems, namely: imipenem, meropenem, ertapenem and doripenem became the antimicrobials of last resort used in treating infections due to these highly drug resistant bacteria [2]. These antimicrobial agents became crucial in the management of life threatening healthcare associated and community acquired infections.…”
Section: Introductionmentioning
confidence: 99%
“…The carbapenems, namely: imipenem, meropenem, ertapenem and doripenem became the antimicrobials of last resort used in treating infections due to these highly drug resistant bacteria [2]. These antimicrobial agents became crucial in the management of life threatening healthcare associated and community acquired infections.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found a higher prevalence for this particular mutation (Mulvey et al 2005;Jorgensen et al 2010;Mammeri et al 2010;Alonso et al 2016), with one reporting a prevalence of 100% (Bogaerts et al 2010). There were two strains (SW-007 and TR-032) that were found to have insertions (thymine) at position -20.…”
mentioning
confidence: 84%
“…Estos resultados son consistentes con otros estudios 9,33 . La resistencia en K. pneumoniae, se asoció a BLEE; sin embargo, la ausencia de AmpC, podría estar subestimada, ya que en este estudio no se buscaron AmpC plasmidiales, siendo la CMY-2 en particular, prevalente a nivel mundial, tanto en cepas de pacientes hospitalizados como en ambulatorios 34,35 . Por otra parte, E. cloacae se asocia principalmente a sobrexpresión de AmpC, aunque es posible encontrar cepas con BLEE y AmpC simultáneamente.…”
Section: Artículo Originalunclassified